2022
DOI: 10.2478/jtim-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of physical activity on cardiometabolic diseases in obese children and adolescents

Abstract: In the past few decades, obesity in the pediatric population has dramatically increased and is common in many countries. Childhood obesity often causes health problems and increases the risk of cardiometabolic diseases such as type 2 diabetes, nonalcohol fatty liver, and cardiovascular diseases. Obesity in young people has been closely associated with environmental, behavioral, and genetic defects, including the availability of high-energy and sugary food and beverages, sedentary behavior, and hereditary facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Studies show that decreases in BMI and other anthropometric parameters are positively associated with physical exercise implemented in school environments, according to interventions of 12 weeks or 60 sessions, which corroborate our results. 12,23,29,42,43 The types of physical exercises implemented in this study are in line with other similar studies also showing a decreased effect on the thickness of tricipital and subscapular skinfolds in body fat composition; in the measurements of the arm, waist, and NC; and in blood glucose levels, producing a positive impact on the control of body mass. 23,29 These measures decrease because of increased energy expenditure produced by physical exercises involving large muscle groups, which positively affect body mass control.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Studies show that decreases in BMI and other anthropometric parameters are positively associated with physical exercise implemented in school environments, according to interventions of 12 weeks or 60 sessions, which corroborate our results. 12,23,29,42,43 The types of physical exercises implemented in this study are in line with other similar studies also showing a decreased effect on the thickness of tricipital and subscapular skinfolds in body fat composition; in the measurements of the arm, waist, and NC; and in blood glucose levels, producing a positive impact on the control of body mass. 23,29 These measures decrease because of increased energy expenditure produced by physical exercises involving large muscle groups, which positively affect body mass control.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also demonstrated the efficiency of 12-week aerobic and resistance exercise programs, combined or not, in reducing blood glucose, lipid, and blood pressure levels in adolescents, indicating both cardiovascular and metabolic benefits. 10,12,[45][46][47][48] These results may be explained by the increased energy expenditure produced by physical exercise that provides cardiorespiratory adaptations, guaranteeing the supply of substrates to the muscles, increasing insulin sensitivity, and stimulating the production of cytokines capable of influencing anti-inflammatory actions and inflammatory and metabolic parameters deranged by excess adipose tissue. 12,47 Regarding blood pressure, regular physical exercises increase endothelial vasodilator capacity, and positively affecting blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations